Promoting classroom participation through micro-credentials certifications - Teoh, Xi Sheng (Nanyang Technological University, 2024)
Adopting technology in education has inspired innovative teaching methods, including gamification and using micro-credentials to enhance learning. This project aimed to develop EduQuest, a web application designed to gamify the learning experience with digital badges. EduQuest enables instructors to manage courses while tracking student progress through integrations with external tools such as Wooclap. Additionally, EduQuest allows students to generate personalised questions based on their learning materials to improve the learning experience further.